2019
DOI: 10.1101/680900
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rescue of Tomato spotted wilt tospovirus entirely from cDNA clones, establishment of the first reverse genetics system for a segmented (-)RNA plant virus

Abstract: The group of negative strand RNA viruses (NSVs) includes not only dangerous pathogens of medical importance but also serious plant pathogens of agronomical importance. Tomato spotted wilt tospovirus (TSWV) is one of those plant NSVs that cause severe diseases on agronomic crops and pose major threats to global food security. Its negative-strand segmented RNA genome has, however, always posed a major obstacle to molecular genetic manipulation. In this study, we report the complete recovery of infectious TSWV en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…TSWV is a temperature-sensitive virus; in fact, depending on the isolate, the thermal inactivation points vary from 40 to 46 • C, with an exposure time of approximately 10 min [223]. TSWV infects a wide range of agricultural crops, including tomato [224,225], where it is responsible for the spotted wilt disease. TSWV is spread in all Mediterranean countries apart from Morocco [226] and may cause from 40-90% and up to 95% loss in yield and marketable value of tomato, respectively [46,47].…”
Section: Tomato Spotted Wilt Virusmentioning
confidence: 99%
“…TSWV is a temperature-sensitive virus; in fact, depending on the isolate, the thermal inactivation points vary from 40 to 46 • C, with an exposure time of approximately 10 min [223]. TSWV infects a wide range of agricultural crops, including tomato [224,225], where it is responsible for the spotted wilt disease. TSWV is spread in all Mediterranean countries apart from Morocco [226] and may cause from 40-90% and up to 95% loss in yield and marketable value of tomato, respectively [46,47].…”
Section: Tomato Spotted Wilt Virusmentioning
confidence: 99%
“…The beginning of the infection cycle of TSWV requires at least RNP, which is the smallest infectious unit of the virus, and the N protein of TSWV is absolutely necessary for the remodeling of the infectious RNP complex. 33 When the data of three different activities (curative, protective, and inactivation) of the target compounds are compared against TSWV in vivo, it was found that the same compound was more effective in the inactivation activity; that is, the compound interacted with the virus and then inactivated the virus to inhibit the spread of the virus. Therefore, to investigate the potential action mode of the target compounds to inhibit TSWV, the real RNP composition was simulated by infecting N. benthamiana with L (+)opt + SR (+)eGFP + VSRs mediated by A. tumefaciens in vivo.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The fluorescence quantity and intensity of N. benthamiana were observed by a fluorescence microscope on the third and fifth days. 33 Expression of α-Enhanced Green Fluorescent Protein (α-eGFP) in Tobacco Was Detected by Western Blot. The sample was removed from −80 °C, and 1.0 g of sample was added to 1.0 mL of protein extraction buffer [50 mL; 5 mL of glycerin, 1.25 mL of 1 M Tris−HCl (pH 7.5), 18.6 mg of disodium ethylenediaminetetraacetic acid (EDTA), 438 mg of NaCl, 77 mg of dithiothreitol, 1 g of polyvinylpolypyrrolidone (PVPP), 0.25 mL of Triton X-100, and 1× protease inhibitor, white and muddy].…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Only recently have the first reverse genetics systems been established for TSWV and RRV. The first one was established for TSWV [ 261 ], soon followed by the establishment of one for RRV [ 95 ]. For both viruses, particles and a systemic infection could be rescued entirely from cDNA clones.…”
Section: Discussionmentioning
confidence: 99%
“…There are no studies that address how microevolution affects any of the aforementioned taxa, largely because reverse genetics platforms have only recently become available [ 75 , 95 , 261 ]. On the other hand, there are investigations on how recombination, reassortment, and genome plasticity affect virus macroevolution.…”
Section: Evolutionmentioning
confidence: 99%